A Shariah guide for sustainable energy production: Microbial Fuel Cells (MFCs) in focus - Zainan Nazri, Nurul Jannah; Nik Mohd Kamal, Nik Nur Madihah; Jani, Mohd. Shah; Fatah Yasin, Raudlotul Firdaus (International Institute for Halal Research and Training (INHART), International Islamic University Malaysia, 2018)
In pursuit of developing a sustainable green energy, the questions of Shari'ah's roles arises. The study applies analytical and inductive method to examine the two sources of Shari'ah; Qur'anic verse, and Prophetic hadith, in order to emphasize on the importance of Shari'ah in the green energy development. Therefore, Microbial Fuel Cells (MFCs) is selected as a model to investigate the theory of Maqasid Shari'ah as to arrive to a comprehensive ethical approach to science. With regards to scientific procedures, Islam emphasizes the preservation of balance in an ecosystem as highly as providing solution. Most importantly, Shari'ah is not only confined to physical and empirical data as it also incorporates spirituality into the equation of a well-designed technology, particularly green energy. Hence, the finding of this study will bring about a set of guidelines to prove that Shari'ah is an essential feature to generate a type of halal energy that shall not only spur economic growth and sustainable development of the nation, but also one that is in harmony with the local environment as well as the global welfare at large.